A Prospective Study of Shortened Vitamin Supplementation Prior to Cisplatin–Pemetrexed Therapy for Non-Small Cell Lung Cancer. (26th September 2014) - Takagi, Yusuke; Hosomi, Yukio; Sunami, Kuniko; Nakahara, Yoshiro; Okuma, Yusuke; Yomota, Makiko; Shimokawa, Tsuneo; Nagamata, Makoto; Iguchi, Mari; Okamoto, Hiroaki; Okamura, Tatsuru; Shibuya, Masahiko
Abstract: Background: Prior supplementation with folic acid and vitamin B12 is required to reduce pemetrexed therapy toxicity; the recommended lead-in time is at least 7 days. On the basis of previous pharmacokinetic and clinical studies, we hypothesized that the lead-in time could be shortened to 24 hours, enabling earlier commencement of standard chemotherapy; thus, we planned the first prospective trial of this regimen. Methods: Patients with advanced nonsquamous non-small cell lung cancer who had not previously received cytotoxic chemotherapy were enrolled. After measurement of homocysteine concentrations, the patients received 1, 000 μg of vitamin B12 by intramuscular injection and began taking 350–500 μg of oral folic acid daily. Starting 24–48 hours after the vitamin B12 injection, the patients received intravenous 500 mg/m 2 pemetrexed and 75 mg/m 2 cisplatin for 4 cycles at 3 weekly intervals. The primary endpoint was the proportion of patients who developed neutropenia grade ≥3. Results: Thirty patients received chemotherapy starting within 48 hours of the vitamin B12 injection. No treatment-related deaths or grade 4 toxicity occurred. Neutropenia grade ≥3, other laboratory toxicities grade ≥3, and nonlaboratory toxicities grade ≥3 occurred in 6.7%, 13%, and 13% of patients, respectively. The baseline homocysteine concentrations were not higher in patients with grade ≥3 toxicities than in the remainder of the cohort (mean values, 8.6 and 10.7 μmol/L, respectively). The response rate to chemotherapy was 43%. Conclusion: The shortened vitamin supplementation was well tolerated and retained antitumor efficacy. Analysis of baseline homocysteine concentrations confirmed the efficacy of short-term vitamin supplementation. Abstract : This study hypothesized that the lead-in time of folic acid and vitamin B12 supplementation prior to pemetrexed therapy could be shortened to 24 hours, enabling earlier commencement of chemotherapy. In this prospective study, the shortened vitamin supplementation was well tolerated and retained antitumor efficacy.